Anteroposterior balance reactions in children with spastic cerebral palsy. (2nd March 2020) - Crenshaw, Jeremy R; Petersen, Drew A; Conner, Benjamin C; Tracy, James B; Pigman, Jamie; Wright, Henry G; Miller, Freeman; Johnson, Curtis L; Modlesky, Christopher M
Abstract : Aim: To compare anterior and posterior standing balance reactions, as measured by single‐stepping thresholds, in children with and without spastic cerebral palsy (CP). Method: Seventeen ambulatory children with spastic CP (eight males, nine females) and 28 typically developing children (13 males, 15 females; age range 5–12y, mean [SD] 9y 2mo [2y 3mo]), were included in this cross‐sectional, observational study. Balance reaction skill was quantified as anterior and posterior single‐stepping thresholds, or the treadmill‐induced perturbations that consistently elicited a step in that direction. In order to understand the underlying mechanisms of between‐group differences in stepping thresholds, dynamic stability was quantified using the minimum margin of stability. Ankle muscle activation latency, magnitude, and co‐contraction were assessed with surface electromyography. Results: We observed an age and group interaction for anterior thresholds ( p =0.001, partial η 2 =0.24). At older (≈11y; p <0.001, partial η 2 =0.48), but not younger (≈7y; p =0.33, partial η 2 =0.02) ages, typically developing children had larger anterior thresholds than those with CP. In response to near‐threshold anterior perturbations, older typically developing children recovered from more instability than their peers with CP ( p =0.004, partial η 2 =0.18). Older children had no between‐group differences in ankle muscle activity. No between‐group differences were observed in posterior thresholds. Interpretation: The effects of CP on balance reactions are age‐ and direction‐specific. Older typically developing children are more able or willing to withhold a step when unstable. What this paper adds: Children with spastic cerebral palsy have age‐ and direction‐specific balance‐reaction impairments. Lower anterior stepping thresholds were observed in older, but not younger children. Older typically developing children withheld a forward step at higher levels of instability. No between‐group differences were seen in posterior stepping thresholds. What this paper adds: Children with spastic cerebral palsy have age‐ and direction‐specific balance‐reaction impairments. Lower anterior stepping thresholds were observed in older, but not younger children. Older typically developing children withheld a forward step at higher levels of instability. No between‐group differences were seen in posterior stepping thresholds. Anterior stepping thresholds represent the perturbation size (as pictured on left) that consistently elicited a step in that direction. We observed an age by group interaction on thresholds such that older children with CP had smaller thresholds than typically developing peers (right).